Climate risk management: The case of forecasting tropical cyclones - CHANG, Carolyn W (Institutional Knowledge at Singapore Management University, 2010)
Global warming has induced an increasing number of deadly tropical cyclones with a continuing trend. Developing high-functional climate risk management tools in forecasting, catastrophe modeling, pricing and hedging is thus crucial. By using transactional price changes of traded hurricane derivatives as the predictor in a doubly-binomial pricing framework, we develop a dynamic market-consensus hurricane forecasting model. Our model can forecast when and how a hurricane will make landfall, and how these forecasts will update themselves upon trading arrival.